Análise da produtividade científica dos docentes da Universidade Estadual Paulista, campus de Marília/SP - Herculano, Rondinelli Donizetti [UNESP]; Norberto, Ana Maria Q. (Escola de Ciência da Informação da UFMG, 2012)
O objetivo do presente trabalho foi analisar/quantificar a produtividade científica dos docentes pertencentes à Universidade de Estadual Paulista (UNESP), campus de Marília/SP. Para cada professor, analisamos o número total de artigos na plataforma Lattes, no ISI Web of Science e no SCOPUS. Além disso, verificamos o total de livros publicados, capítulos de livros publicados e orientações em Programas de Pós-Graduação (PPG). A análise dos nove departamentos da Faculdade de Filosofia e Ciências (FFC) mostrou que o Departamento de Ciências Políticas e Econômicas possui uma média elevada (21,42) de artigos na Plataforma Lattes, quando comparado aos outros departamentos. Entretanto, o Departamento de Fonoaudiologia apresentou médias mais altas em artigos indexados pelo ISI (2,61) e SCOPUS (4,39), bem como o índice-h, nessas plataformas. em relação aos programas de pós-graduação, o Departamento de Administração e Supervisão Escolar foi o que apresentou a maior média de orientações em andamento e/ou concluídas. O desempenho mais baixo, em relação aos artigos publicados pelo ISI e SCOPUS, pelos departamentos na área de Humanas/Humanidades pode estar associado às características do campo da concentração e da cobertura limitada do banco de dados ISI e SCOPUS, indicando que o índice-h é muito sensível ao campo de concentração.

In this work, an analysis of scientific bibliographic productivity was made using the Faculdade de Filosofia e Ciências, Universidade Estadual Paulista (FFC-UNESP) as example. It is composed by nine departments which offer altogether nine undergraduate courses: 1) Archival, 2) Library, 3) Speech Therapy, 4) Pedagogy, 5) International Relations, 6) Physiotherapy, 7) Occupational Therapy, 8) Philosophy, 9) Social Sciences and six graduate programs leading to M.S. and Ph.D. degrees. Moreover, when analyzing the different courses of FFC-UNESP, they represent typical academic organization in Brazil and Latin America and could be taken as a model for analyzing other Brazilian research institutions. Using data retrieved from the Lattes Plataform database (Curriculum Lattes) we have quantitatively the scientific productivity percentage of professors at UNESP. We observed that bibliometric evaluations using the Curriculum Lattes (CL) showed that the professors published papers in journal are not indexed by ISI and SCOPUS. This analysis was made using: 1) the total number of papers (indexed in Curriculum Lattes database), 2) the number of papers indexed by Thomson ISI Web of Science database and SCOPUS database, and 3) the Hirsch (h-index) by ISI and SCOPUS. Bibliometric evaluations of departments showed a better performance of Political Science and Economics Department when compared to others departments, in relation total number of papers (indexed in Curriculum Lattes database). We also analyzed the academic advisory (Master's Thesis and Ph.D. Thesis) by nine departments of FFC/UNESP. The Administration and School Supervision Department presented a higher academic advisory (concluded and current) when compared to the others departments.
Scientific research output evaluation of professors of São Paulo State University, Marília/SP
Keywords: Cienciometria; Indicadores de produção científica; Bibliometria; Periodical index; Scientific publication indicators; Scientometrics